Impact of Russia- Ukraine War on Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In this day and age, few individuals have considered making war predictions. Still, it is taking place. Both the global economy and the people of Ukraine are suffering as a result of something they have never done in their lives.Ukraine was attacked by Russia on February 24, 2022. Since then, Russia has been the target of criticism from other nations as a whole, and now, other nations have united against Russia, greatly impacting the global economy.My research attempts to determine how the ongoing conflict between Russia and Ukraine has influenced India's international commerce, what effects it has had on the country's future, and what other patterns the Indian economy will likely follow as a result of this conflict. I'll examine India's international commerce with Russia and Ukraine during the last five years and attempt to research how a conflict would affect trade in the future. We believe that this study article will aid in the understanding of the global impact of this conflict by the scholarly community.